Statistical and fractal analyses of autofluorescence of myocardium tissue images in diagnostics of acute coronary insufficiency - Dubolazov, O.V.; Sidor, M.I.; Karachevtsev, A.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
This research presents the results of investigation of laser polarization fluorescence of biological layers (histological sections of the myocardium). The polarized structure of autofluorescence imaging layers of biological tissues was detected and investigated. Proposed in this work is the model for describing formation of polarization inhomogeneity in autofluorescent images of biological optically anisotropic layers. On its basis, analytically and experimentally tested is the method of laser autofluorescent polarimetry. Analyzed has been the effectiveness of this method in the postmortem diagnosis of infarction. The objective criteria (statistical moments) of differentiation of autofluorescent images of histological sections myocardium have been determined. The operational characteristics (sensitivity, specificity, accuracy) of this technique have been ascertained.